1973
DOI: 10.1002/chin.197336292
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: DARST. DER DIAETHYLBORSAEUREESTER VON ALKANNITRONSAEUREN

Abstract: Nitroolefine (I) vermischt man in ätherischer Lösung bei 30 ‐ 35°C mit Triäthyl bor (II) und kühlt nach einigen Stunden auf ‐70°C. Dabei kristallisieren die Ester (IIIa)‐(IIIc) aus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Reactions of conjugated nitroalkenes with different kinds of organometallic reagents derived from lithium, magnesium, zinc, aluminum, copper, and boron yielding nitroalkanes or carbonyl compounds have been well studied . It is reported that β-nitrostyrenes react with dialkylzinc, organomanganese, t -BuHgX/KI, or trialkylgallium reagents, respectively, to generate alkenes and/or nitroalkanes, and the mechanism is proposed to be an ionic 3 or free-radical reaction. , Barton has shown that thiopyridone-based esters react with nitroolefins to generate α-nitro sulfides by free radical chain reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions of conjugated nitroalkenes with different kinds of organometallic reagents derived from lithium, magnesium, zinc, aluminum, copper, and boron yielding nitroalkanes or carbonyl compounds have been well studied . It is reported that β-nitrostyrenes react with dialkylzinc, organomanganese, t -BuHgX/KI, or trialkylgallium reagents, respectively, to generate alkenes and/or nitroalkanes, and the mechanism is proposed to be an ionic 3 or free-radical reaction. , Barton has shown that thiopyridone-based esters react with nitroolefins to generate α-nitro sulfides by free radical chain reactions .…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our study of the reactions of β-nitrostyrenes with triethylaluminum, not only the ionic products 1-nitro-2-arylbutanes but also the free-radical products 1-aryl-1-butenes were formed in etheral solvent . All these results indicate that conjugated nitroalkenes are useful intermediates in organic synthesis and may react with nonstabilized nucleophiles to generate different products under different workup conditions. In this paper, we wish to report the first example of the reactions of the β-nitrostyrenes with trialkylboranes to generate alkenes by alkyl substitution of NO 2 .…”
Section: Introductionmentioning
confidence: 99%